ANALISIS PENDAPATAN PETANI MELALUI SISTEM INTEGRASI TANAMAN PADI-TERNAK SAPI DI DESA JARO KECAMATAN JARO KABUPATEN TABALONG (STUDI KASUS PADA KELOMPOK TANI “TANI MEMBANGUN”) - Purna Kusumayana; Arlina Arlina (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
This Research aims to determine how much it costs, revenue and income of farmers through an integration system of rice-breeding cattle crops in the farmers group “Tani Membangun” in Jaro village Jaro District Tabalong Regency. The method used is observation method, data collection was conducted from March until June 2015. The data analysis used is quantitative analysis. Quantitative data includes the revenue and expenses incurred farmers in the integration system of rice-breeding cattle crops such as variable costs and fixed costs. Element of total revenue and total cost of measurement is based on the measurement indicators. Descriptive statistical analysis is the analysis of the data used in this research to calculate the average income. The results of this research shows that the total costs is Rp.37.527.195,-/year, total revenue in the amount Rp.90.025.454,-/year and the income earned Rp.56.170.067,-/year with an average area of land owned 0,8 ha and 2,6 livestock ownership and production of livestock waste (fases) in the form organicfertilizer 711,6 kg/year.